Perspectives on the utilization of Azolla-Anabaena system as feed supplement - ABRAHAM, GERARD; JAISWAL, PRANITA; SINGH, YUDH VIR; YADAV, RAVINDRA KUMAR; KUMAR, RAVINDRA; MUDGAL, VISHAL; SINGH, PAWAN KUMAR (The Indian Journal of Animal Sciences, 2021)
The nitrogen fixing aquatic pteridophyte Azolla is one of the fastest growing nitrogen-fixing plants and it is used as a potential source for high rate biomass production. Azolla has the ability to fix atmospheric nitrogen at cheaper and faster rates due to the presence of a symbiotic cyanobacterium Anabaena azollae. Therefore, the ability to fix atmospheric nitrogen is important from an agricultural perspective. However, Azolla is gaining popularity as feed supplement for cattle, poultry and fish. Further, the ease of cultivation and favourable nutrient composition make Azolla an important feed supplement. This review focuses on the perspectives of Azolla as feed supplement.